Feasibility of an alternative method to estimate glenohumeral joint center from videogrammetry measurements and CT/MRI of patients. Issue 1 (20th May 2021) - Sarshari, Ehsan; Mancuso, Matteo; Terrier, Alexandre; Farron, Alain; Mullhaupt, Philippe; Pioletti, Dominique
Abstract: Videogrammetry is commonly used to record upper limb motions. However, it cannot track the glenohumeral joint center (GH). GH is required to reconstruct upper limb motions. Therefore, it is often estimated by separately measuring scapular motions using scapular kinematics measurements devices (SKMD). Applications of SKMD are neither straightforward nor always noninvasive. Therefore, this work investigates the feasibility of an alternative method to estimate GH from videogrammetry using a CT/MRI image of subject's glenohumeral joint and without requiring SKMD. In order to evaluate the method's accuracy, its GH estimations were compared to reference GH trajectories. The method was also applied to estimate scapular configurations and reconstruct an abduction motion measured by videogrammetry. The accuracy of GH estimations were within 5 mm, and the reconstructed motion was in good agreement with reported in vivo measurements.